Increasing Learning Outcomes through the Student Team Heroic Leadership and Provision of Structured Tasks Strategies - Nasir S; Sriyanti Mustafa; Mamad Ahmad (Edukasi, 2022)
Learning in schools is not only intended to achieve educational goals for certain lessons but also to equip students to master the concept of material and apply it in everyday life. Moreover, learning is also intended to achieve educational goals as a whole general which is formal, namely, to organize students' reasoning and shape their personalities. This research is classroom action research that aims to improve learning outcomes through student team heroic leadership strategies and the provision of structured assignments. The subjects in this study were students of class X.2 MA DDI Kaballangang, Pinrang. This research is Classroom action research carried out in two cycles. Data collection using learning outcomes tests sheets and observation sheets. The collected data is analyzed using quantitative analysis techniques and qualitative analysis, presenting information, and drawing conclusions. The results showed that there was an increasing learning outcome through student team heroic leadership strategies and the provision of structured assignments which was marked by an increase in the average score of student learning outcomes from cycle 1 to cycle 2, which was 61.28 increasing to 83.72, student learning completeness in the second cycle. I which has not been achieved classically only reached 48.3%, but in cycle 2, classical completeness was achieved, namely 89.7% so there was an increase in the percentage of student activity in the learning process from cycle 1, namely 35.28% to cycle 2, namely 47.32%